Pátria, nação, povo brasileiro na produção didática de Manoel Bomfim e Olavo Bilac: Livro de Leitura (1899) e Atravez do Brasil (1910) - Santos, Alexsandro do Nascimento (2010)
This research examined the didactic production of Manoel Bomfim and Olavo Bilac, choosing the works Prática da Lingua Portugueza Livro de Leitura para o Curso Complementar (1899) e Atravez do Brasil Livro de Leitura para o Curso Médio (1910). In view of cultural studies and based on the understanding of the textbook as a cultural product and a device powered by the State for the production and dissemination of a cultural selection, which among other things, points out memories and identities considered legitimate for the nation, investigated are the contexts of production and circulation of these two works, outlining his entry in the history of teaching s editions and the process of institutionalization of the school in Brazil (late nineteenth and early twentieth century) in which gain prominence and public agenda in the intellectual struggles surrounding the narratives about the homeland , the nation and around the binominal race/Brazilian people. The privileged sources during the investigation beyond the works themselves were the biographies of the authors and their bibliographies, biographies of the editor (Francisco Alves) produced by scholars of the period, records of contemporary writers to authors, especially those tied to their networks of sociability (in autobiographies or equivalent) and catalogs editorials, studies and research on the history of teaching s editions in Brazil and the debate around the issue of race that established itself as the public agenda in the period. For the treatment of sources, we attempted to establish dialogue between the records and voices of the discourse in order to identify theirs points of similarity, contradiction and mutual understanding. The investigation concluded that the works were produced and circulated in the context of the institutionalization of school in Brazil where the textbooks have become more specific contours and in the field of teaching reading, vie for hegemony on the formal model, the anthologies, narratives in single book, books in series and the contract activity, and the first of the works studied fits the model and the second anthology of works fits into the narrative model into a single book. Concluded further that the treatment given to issues of nationality, country and race / Brazilians in the two works presents a narrative that legitimized the independence of Brazil as the nation's founding in march, not giving treatment, or even explicitly laudatory applicant to the Republic, builds and presents a territory particularly rich and valuable from the standpoint of natural and also the constructions of 'progress' (railroads, construction of infrastructure, industries), shall elect as a model of the Brazilian people the scrub type, preserving the distinction between the scrub and the backcountry coastal scrub, but proposing an interpretation of these two types as 'moments' evolution of the nation and outlines a different approach to arrays black / African, Indian and Portuguese / European in the formation of Brazilian nationality in which the first is recognized as a victim of slavery, but valuable for this patriotism, his ability to work and their participation in the civilizing process and the second is outlined as naive, bellicose, tough to civilization, but should it be earned